Performance comparison between LQG and PID controllers for HDD's servo timing control system / Ng Yap Han - Ng , Yap Han (2018)
The growth of technology in the cloud system namely Artificial Intelligence (AI) and Big Data nowadays has pushed the memory storage capacity to grow rapidly above 10% every year, as IBM has predicted the demand for data scientist will grow 28% by year 2020 [1]. The challenge for HDD maker today is to increase the areal density (the number of bytes of bytes per information to be stored per surface area of the disk), and when the areal density gets higher in the same dimension size on the media, the inch per tracks significantly reduces which in turn becomes a challenge to servo design engineers [19]. The accuracy of control system in HDD needs to be able to reject disturbance efficiently to maintain the least steady-state error. HDD is vastly adopting the technology which uses PID controller to achieve the performance, nevertheless it is believed that there is much room for improvement on the performance using the new method, Linear Quadratic Regulator with Kalman Filter (LQG) [20]. In this thesis, LQG will be analyzed against existing PID control in HDD which sees a 30% improvement on NRO Phase Rejection.